Laboratory Identification of Arthropod Ectoparasites - Mathison, Blaine A. (American Society for Microbiology, 2014)
SUMMARY: The collection, handling, identification, and reporting of ectoparasitic arthropods in clinical and reference diagnostic laboratories are discussed in this review. Included are data on ticks, mites, lice, fleas, myiasis-causing flies, and bed bugs. The public health importance of these organisms is briefly discussed. The focus is on the morphological identification and proper handling and reporting of cases involving arthropod ectoparasites, particularly those encountered in the United States. Other arthropods and other organisms not of public health concern, but routinely submitted to laboratories for identification, are also briefly discussed.